AKIBAT PENGGOLONGAN HUKUM TERHADAP PEMBUATAN SURAT KETERANGAN HAK WARIS DI KALANGAN NOTARIS - ALBERT ALBERT ALBERT (PREMISE LAW JURNAL, 2017)
As a country which has been under Dutch colonialism, Indonesia undergoes negative access of the diversity of pluralistic society.Classification or division was systematically and structurally done by the Dutch East Indies Government. One of the excesses of colonialism was different judicial division for each group of the people in Indonesia which was the European, the Foreign East, and the Natives; each of them had its own judicial classification in the Civil Code and customary law. The research used judicial normative and descriptive analytic methods by analyzing. That not all of the Indonesian people need notarial deeds in a certain legal act. It is intended only for the Foreign East Chinese who need inheritance right certificates and the other legal acts which need notarial deedsThe implementation of classification system of law for the Indonesian citizens in the practice of drawing up notarial deeds is guided by judicial classification for the Indonesian people made by the Dutch East Indies Government which is in effect although Law No. 12/2006 on the Citizenship of the Republic of Indonesia has been issued.   Keywords: Judicial Classification, Citizen, Inheritance Right Certificate